Identifikasi Metabolit Sekunder Ekstrak Etil Asetat Biji Alpukat (Persea americana Mill.) dan Uji Toksisitas Terhadap Larva Udang Artemia salina Leach. - Nurdia Asdar; Asriani Ilyas; Maswati Baharuddin (Al-Kimia, 2014)
Identification of metabolite compound in acetone Extract from Fruits Avocado seed (Percea americana Mill) and toxicity test against Artemia salina Leach. Aim of this research is to identify the secondary metabolite compound in aceton extract from fruits Avocado seed (Percea americana Mill) and to determine the potential of secondary metabolites from an avocado extract as anticancer. The compound was obtained from Identification process in several stages, namely extraction, fractination, purification and identification. The identification process was color test, TLC, spectroscopy IR. The toxicity test by Brine Shrimp Lethality Test (BSLT) to Artemia salina Leach. The compound obtained from this research was yellow-white crystalline needle-shaped, the purity test with TLC analysis showed a stain in three eluen system on the stain test on three eluent systems with Rf proportions as follows; 0,15 from chloroform:ethyl acetat (6:4), 0,33 from methanol:chloroform (1:9), 0,75 for acetone:ethyl acetat, and positively to the reagent Wagner and gave brown precipitate for indicate as alcaloid group. This result is supported by spectroscopy from compound.While toxicity tests showed condensed acetone extracts  and pure compounds are toxic with LC50 value of each is 20.61 mg/mL and 39,81 mg/mL.